2014
DOI: 10.5846/stxb201207080957
|View full text |Cite
|
Sign up to set email alerts
|

Effect of grazing intensity on temperature sensitivity of soil nitrogen mineralization in Zoigё alpine meadow

Abstract: Overgrazing, climate changes, and drainage are the important disturbances and critical environmental problems for Zoig刈 alpine meadow. These factors play an important role in regulating the soil nitrogen ( N) cycle and to some extent influence alpine meadow ecosystem structure and function. In this study, we investigated the effect of grazing intensity on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Previous studies have revealed that plant C, N and P contents relate to numerous abiotic and biotic factors, including plant growth stage (Elser et al 2000), grazing (Zheng et al 2012, Zhang et al 2014, and plant functional traits (Reich et al 1999). As such, studies often investigate the changes in N, C and P in accordance with a single ecological factor at the regional scale or in one habitat (Niu et al 2013.…”
mentioning
confidence: 99%
“…Previous studies have revealed that plant C, N and P contents relate to numerous abiotic and biotic factors, including plant growth stage (Elser et al 2000), grazing (Zheng et al 2012, Zhang et al 2014, and plant functional traits (Reich et al 1999). As such, studies often investigate the changes in N, C and P in accordance with a single ecological factor at the regional scale or in one habitat (Niu et al 2013.…”
mentioning
confidence: 99%